Implementation of Madrasah Supervisor: a Case Study at the Banyumas Public and Private Madrasah Schools - Munjin Munjin; Zidni Rosyadi (Al-Hayat Al-Istiqomah Foundation collab with Letiges, 2021)
This study aims to describe and analyze the managerial supervision activities carried out by madrasah supervisors towards madrasah principals in the Banyumas district. This type of research is qualitative case studies, data collection administrative supervision using in-depth interviews, observation and documentation. The data sources used as informants were the head of the supervisory group, the supervisors of the madrasah tsanawiyah, the leaders of madrasahs and staff. Then, the data collected is analyzed using data reduction, data display, and conclusions as in Miles and Huberman's theory. Based on the research results, it is known that managerial supervision activities are in a good position with a score range between 80-90. These activities include monitoring, assessment and evaluation, coaching, and follow-up. However, in remote Madrasah, the supervision was not optimal because the ratio between supervisors and Madrasah was less than ideal.